THE INFLUENCE OF HIGH PERFORMANCE WORK SYSTEM (HPWS) ON EMPLOYEE PERFORMANCE AT PT BANK NEGARA INDONESIA (PERSERO) JABABEKA BRANCH OFFICE - Irena D Silva; Agung Surya Dwianto (JURNAL ECONOMINA, 2026)
This study examines the effect of High Performance Work System on employee performance at the Jababeka Branch of PT Bank Negara Indonesia (Persero) Tbk located in a high-intensity industrial service environment. As banking competition and service expectations increase, integrated human resource practices become critical to sustain operational accuracy, speed, and professionalism at the branch level. Grounded in the Ability, Motivation, and Opportunity framework, this research conceptualizes High Performance Work System through ability-enhancing, motivation-enhancing, and opportunity-enhancing practices embedded in job design and work systems. A quantitative approach was employed using Likert-scale questionnaires distributed to 150 employees selected through purposive sampling. Data were analyzed using simple linear regression. The results indicate that High Performance Work System has a positive and significant effect on employee performance, supported by a strong standardized coefficient and high statistical significance. The coefficient of determination shows that the model explains more than half of the variance in employee performance, while the remainder is influenced by contextual organizational factors. These findings confirm that systematic implementation of integrated human resource practices directly strengthens timeliness, service quality, work efficiency, and professionalism among frontline banking employees operating under operational pressure. The study contributes empirical evidence from a branch-level banking context and offers practical insight for managers in designing human resource systems that align employee capability, motivation, and opportunity with service performance demands.